İç borçlanma politikasının gelir dağılımı üzerindeki etkisi - Soğancılar, Emre (My University, 2007)
İç Borçlanma Politikasının Gelir Dağılımı Üzerindeki Etkisi Gelişen sosyal devlet anlayışıyla, devletin görev ve sorumlulukları genişlemekte, sunmak zorunda olduğu hizmetlerde artış ve çeşitlilik yaşanmaktadır. Artan kamu hizmetleri, devlet harcamalarında yükselişe nedABSTRACT The Effect of Internal Debt on Income Distiribution With thriving social state concept, government’s duty and responsibilities have been expanding; and services that it has to provide have been getting diversified and increased. As the consequence of increased public services, state’s expenditures have risen and funding of these expenditures has become important. Borrowing policy that the government pursues has created permanent influence on the economy and private individuals. State indebtedness has been a theme highly interesting and debatable not only in our country, but also in many other countries. Internal debts have constituted the most substantial part of state indebtedness which is highlighted mostly from the perspective of intended use and its financial burden on the government and citizens. Because of the fact that indebtedness ,which is used to cover financial deficit, has an influence on not only the relevant generation, but also on posterity; it has a social dimension besides its economic dimension. İn consideration of dept received, income distribution has an effect to the disadvantage of middle class. While profit, interest and rental income’s portion of national income has been incrising, the portion of agriculture and paid labour has been showing a decrease. The impact of internal dept, which is one of the public deficit financial instruments, on income distribution has been determined as the chief objective of the study. Structure, development and current situation of internal dept have been analyzed and wage lowering impact of internal debt, and debt’s financial management impact on income distribution have been evaluated by using statistical data. en olmakta ve bu harcamaların finansmanı sorunu önem kazanmaktadır. Devletin borçlanma politikası, ekonomi ve ekonomik bireyler üzerinde kalıcı etkiler yaratmaktadır. Devlet borçlanması, ülkemizle birlikte diğer ülkelerde de ilgi çeken ve tartışılan bir konu olmuştur. Kullanım amacı, devlete ve vatandaşlara getirdiği yükler üzerinde durulan borçlanmanın, en önemli kısmını iç borçlar oluşturmaktadır. Finansman yetersizliklerini gidermek için başvurulan borçlanmanın ekonomik boyutu yanında sosyal boyutu da vardır. Çünkü borç yükü sadece borç alan nesli değil,gelecek nesilleri de ilgilendirir.Alınan borçlar sonucunda gelir dağılımının orta sınıf aleyhine sonuçlandığı görülmüştür. Kar, faiz ve kira gelirlerinin milli gelirden aldığı pay artış gösterirken tarım ve ücretli sınıfın payında düşüş yaşanmıştır. Bu çalışmada kamu açıkları finansman araçlarından iç borçların yapısı,gelişimi ve bugünkü durumu analiz edilmiş, çalışmanın ana amacı iç borçlanmanın gelir dağılımı üzerindeki etkisi olarak belirlenmiştir. İç borçların ücretleri düşürme etkisi, borçların finansman yönteminin gelir dağılımı üzerinde yarattığı etkiler, istatistiksel verilerle değerlendirilmeye çalışılmıştır.

The Effect of Internal Debt on Income Distiribution With thriving social state concept, government’s duty and responsibilities have been expanding; and services that it has to provide have been getting diversified and increased. As the consequence of increased public services, state’s expenditures have risen and funding of these expenditures has become important. Borrowing policy that the government pursues has created permanent influence on the economy and private individuals. State indebtedness has been a theme highly interesting and debatable not only in our country, but also in many other countries. Internal debts have constituted the most substantial part of state indebtedness which is highlighted mostly from the perspective of intended use and its financial burden on the government and citizens. Because of the fact that indebtedness ,which is used to cover financial deficit, has an influence on not only the relevant generation, but also on posterity; it has a social dimension besides its economic dimension. İn consideration of dept received, income distribution has an effect to the disadvantage of middle class. While profit, interest and rental income’s portion of national income has been incrising, the portion of agriculture and paid labour has been showing a decrease. The impact of internal dept, which is one of the public deficit financial instruments, on income distribution has been determined as the chief objective of the study. Structure, development and current situation of internal dept have been analyzed and wage lowering impact of internal debt, and debt’s financial management impact on income distribution have been evaluated by using statistical data.
Keywords: Borçlanma; Borçlanma, İç; Ekonomi